A quadrupole ion trap mass spectrometer for dry microparticle analysis. Issue 18 (21st August 2019) - Özdemir, Abdil; Lin, Jung-Lee; Gülfen, Mustafa; Hsiao, Chun-Jen; Chen, Chung-Hsuan
Abstract : In this work, we report a new design of a charge detection quadrupole ion trap mass spectrometer (QIT-MS) for the analysis of micro-sized dry inorganic and bioparticles including red blood cells (RBCs) and different sizes of MCF-7 breast cancer cells. Abstract : In this work, we report a new design of a charge detection quadrupole ion trap mass spectrometer (QIT-MS) for the analysis of micro-sized dry inorganic and bioparticles including red blood cells (RBCs) and different sizes of MCF-7 breast cancer cells. The developed method is one of the fastest methods to measure the mass of micro-sized particles. This system allows the online analysis of various micro-sized particles up to 1 × 10 17 Da. The calibration of the mass spectrometer has been done by using different sizes of polystyrene (PS) particles (2–15 μm). The measured masses of RBCs were around 1.8 × 10 13 Da and MCF-7 cancer cells were between 1 × 10 14 and 4 × 10 14 Da. The calculated mass distribution profiles of the particles and cells were given as histogram profiles. The statistical data were summarized after Gaussian type fitting to the experimental histogram profiles. The new method gives very promising results for the analysis of particles and has very broad application.